Epidemiological overview of surgical treatment of hydrocele in Northeastern Brazil: Analysis of a decade (Research, Society and Development, 2025)
This study aimed to analyze the epidemiological profile of hospital admissions for surgical treatment of hydrocele in Northeastern Brazil from 2015 to 2024. This is a quantitative, descriptive, cross-sectional investigation based on secondary data from the Brazilian Unified Health System’s Hospital Information System (SIH/SUS). A total of 29,690 hospitalizations were identified, with a total cost exceeding R$ 9 million and 44,456 hospital days. The Northeast was the second region with the highest number of procedures, behind only the Southeast. A decline in surgeries was observed in 2020, followed by a recovery through 2024, possibly related to the COVID-19 pandemic. Despite the low mortality rate, the underreporting of deaths stands out as a major limitation. The findings offer relevant insights for public health planning and for strengthening regional surgical care within the SUS.